Effect of Recombinant Prophenin 2 on the Integrity and Viability of Trichomonas vaginalis. (1st March 2015) - Hernandez-Flores, J. L.; Rodriguez, M. C.; Gastelum Arellanez, A.; Alvarez-Morales, A.; Avila, E. E.
Abstract : Trichomonas vaginalis is the causal agent of trichomoniasis, which is associated with preterm child delivery, low birth weight, and an increased risk of infection by human papilloma virus and human immunodeficiency virus following exposure. Several reports have established increasing numbers of trichomoniasis cases resistant to metronidazole, the agent used for treatment, and it is therefore important to identify new therapeutic alternatives. Previously, our group reported the effect of tritrpticin, a synthetic peptide derived from porcine prophenin, on T. vaginalis ; however, the hemolytic activity of this small peptide complicates its possible use as a therapeutic agent. In this study, we report that the propeptide and the processed peptide of prophenin 2 (cleaved with hydroxylamine) affected the integrity and growth of T. vaginalis and that pro-prophenin 2 displays some resistance to proteolysis by T. vaginalis proteinases at 1 h. Its effect on T. vaginalis as well as its low hemolytic activity and short-time stability to parasite proteinases makes prophenin 2 an interesting candidate for synergistic or alternative treatment against T. vaginalis .